Contact spacing controls the on-current for all-carbon field effect transistors - Ali Deniz Özdemir (Nature Portfolio, 2021)
The need for reduced dimensions of future devices pushes the limits of essential Si-based components and so alternative materials, such as carbon nanotubes or graphene, are being investigated as alternatives, but with new materials come new challenges. Here, the authors experimentally and theoretically investigate the on-currents for all-carbon transistors finding that contact spacing and length plays an important role in device performance.